Mucin Expression in Mucinous Pancreatic Cysts: Can String Sign Test Predict Mucin Types? A Single Center Pilot Study - Köker, İbrahim Hakkı and Ünver, Nurcan and Malya, Fatma Ümit and Uysal, Ömer and Biberci Keskin, Elmas and Şentürk, Hakan (Turkish Journal of Gastroenterology, 2021)
Background/Aims: Mucinous pancreatic cystic lesions (PCLs) express different mucin types according to their histomorphologic types. High cystic fluid viscosity may help for detection of mucinous PCLs. We hypothesized that if high cystic fluid viscosity may be suggestive of a certain mucin (MUC) type in mucinous PCLs. Materials and Methods: Prespecified MUC types (MUC1, MUC2, MUC4, MUC5AC and MUC6) were evaluated in 18 definitively diagnosed mucinous PCLs with sufficient tissue material and prediagnostic cyst fluid viscosity evaluation -String Sign (SS)- test. We evaluated the agreement of MUC expression with positive SS test results. Later, we compared cystic fluid carcinoembryonic antigen (CEA) between the prespecified MUC expressing and nonexpressing cyst types. Results: A total of 18 mucinous PCL patients, 11 females, with mean age ± SD (59.7 ± 13.3) were included. Almost all malignant mucinous PCLs expressed MUC1 (71.4 %) (P=0.023). We found no significant agreement between the prespecified MUC types and positive SS, except MUC4 which had a mild agreement. Also, no significant relation was found between cystic fluid CEA levels and MUC expression (p=0.584). Conclusion: We did not detect a significantly moderate or good agreement between the prespecified MUC types and SS test. MUC1 was highly expressed in malignant mucinous cysts however, it was incompatible with the SS test. MUC4 expression showed a mild agreement with SS test in a small number of patients. Cite this article as: Köker İH, Ünver N, Ümit Malya F, Uysal Ö, Biberci Keskin E, Şentürk H. Mucin expression in mucinous pancreatic cysts: Can string sign test predict mucin types? A single center pilot study. Turk J Gastroenterol 7 December 2020. 10.5152/tjg.2020.20060.